Bing-Neel Syndrome Case Report: A Previously Undocumented IgG Variant with MRI, PET/CT, and PET/MRI Imaging. (6th April 2016) - Halperin, Daniel; Hallam, Simon; Haroon, Athar; Butler, Tom; Agrawal, Samir
Abstract : Waldenstrom's macroglobulinaemia is the most commonly reported subtype of lymphoplasmacytic lymphoma (LPL); it is characterised by IgM secretion. Neurological complications are common usually as a result of hyperviscosity. In rare cases, cells can infiltrate the central nervous system; this is known as Bing-Neel syndrome. We report the case of a 57-year-old male with lymphoplasmacytic lymphoma of the IgG-subtype with neurological symptoms and the consequent finding of lymphoplasmacytoid cells in his cerebrospinal fluid as well as deposits on MRI and PET-CT imaging. This is the first report of Bing-Neel syndrome in IgG-subtype LPL. We discuss the biological and radiological markers of his disease, including PET imaging, which has been minimal in this area to date.